Increased Fdg Uptake in Association with Reduced Extremity Fat in HIV Patients. Issue 2 (February 2013) - Torriani, Martin; Zanni, Markella V; Fitch, Kathleen; Stavrou, Eleni; Bredella, Miriam A; Lim, Ruth; Cypess, Aaron M; Grinspoon, Steven
Background: HIV lipodystrophy – characterized by peripheral lipoatrophy, with or without central fat accumulation – confers increased metabolic risk. However, the functional activity of HIV lipodystrophic tissue in relation to metabolic risk has yet to be fully explored in vivo through the use of non-invasive imaging techniques. This study assesses the relationship between FDG uptake in various fat depots and metabolic/immune parameters among subjects with HIV lipodystrophy. Methods: Lipodystrophic men on antiretroviral therapy underwent whole-body 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET)/computed tomography scans and detailed metabolic/immune phenotyping. Results: FDG uptake in the subcutaneous adipose tissue (SAT) of the extremities (mean standardized uptake value [SUV] of the arm and leg SAT) was found to correlate with the degree of peripheral lipoatrophy ( r =0.7; P =0.01). Extremity SAT FDG uptake was positively associated with homeostasis model assessment of insulin resistance (HOMA-IR; r =0.6; P =0.02) and fasting hyperinsulinaemia ( r =0.7; P= 0.01), while fat percentage of extremities was not. Furthermore, extremity SAT FDG uptake was significantly associated with CD4 + T-cell count ( r =0.6; P =0.05). In multivariate modelling for HOMA-IR, extremity SAT FDG uptake remained significant after controlling for body mass index and tumour necrosis factor-α (R 2 for model =0.71, P =0.02; SUV in the extremity SAT β-estimate 12.3, P =0.009). Conclusions: In HIV lipodystrophic patients, extremity SAT FDG uptake is increased in association with reduced extremity fat and may contribute to insulin resistance. Non-invasive assessments of in situ inflammation using FDG-PET may usefully complement histological and gene expression analyses of metabolic dysregulation in peripheral fat among HIV-positive patients.